4(x-1)=6x-9

Simple and best practice solution for 4(x-1)=6x-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-1)=6x-9 equation:



4(x-1)=6x-9
We move all terms to the left:
4(x-1)-(6x-9)=0
We multiply parentheses
4x-(6x-9)-4=0
We get rid of parentheses
4x-6x+9-4=0
We add all the numbers together, and all the variables
-2x+5=0
We move all terms containing x to the left, all other terms to the right
-2x=-5
x=-5/-2
x=2+1/2

See similar equations:

| x1.06=100 | | X^4=-(1+i) | | .06x+x=100 | | 7e+3=80 | | 140=y(6+Y) | | 4(4s+5)=148 | | 6x-7x=+11-1 | | X^4=-1-i | | 7-6c=47 | | 2a/7=42 | | 2(x×6)=7+5 | | (2x=3)(x-1)=1 | | (4^(3x+1))=22 | | 6xxx5=120 | | a+79=718 | | x2-Y2=40 | | 7x/4=3x-10 | | 88/2x=22 | | AxB=54 | | 6(4-9x)-18(3x-2)=60 | | x-1/4=3/4x | | x-14=34x | | 8x–2=-64 | | 5x-20-4x+4=0 | | 50=59(x+5) | | 5(3-2a)+5=-10-5*(5a) | | x+10/100=1/x | | 2xx8=4x+2x6 | | 2(x-3)=3(3x-20) | | 12(7-3x)+6=100-6*(6x) | | 9r+15=3r-21 | | 15(2z+6)-4=6*(5z)+86 |

Equations solver categories